Defect engineering, microstructural examination and improvement of ultrafast third harmonic generation in GaZnO nanostructures: a study of e-beam irradiation. Issue 7 (11th February 2020) - Antony, Albin; P., Poornesh; Kityk, I. V.; Ozga, K.; Jedryka, J.; Myronchuk, G.; Kulkarni, Suresh D.; Sanjeev, Ganesh; Petwal, Vikash Chandra; Verma, Vijay Pal; Dwivedi, Jishnu
Abstract : Electron beam induced effects on defect engineering and structural, morphological and optical properties of Ga doped ZnO (GaZnO) nanostructures for improved ultrafast nonlinear optical properties are presented. Abstract : Electron beam induced effects on defect engineering and structural, morphological and optical properties of Ga doped ZnO (GaZnO) nanostructures for improved ultrafast nonlinear optical properties are presented. A microstructural analysis was carried out based on the Scherrer, Williamson–Hall, and size–strain models. All three models reveal a peak broadening effect upon electron beam irradiation (EBI) and the crystallite size of the films shows a decrease of 30% compared to unirradiated nanostructures. The decrease in intensity, variation in the peak position and broadening of the Raman E2H mode confirm that the EBI treatment introduces disorder into the nanostructures. The interband gap emissions observed in photoluminescence spectra are primarily due to defect-related emissions originating from intrinsic defects such as Zni, Oi, VZn, VO, VZn +, VO + and OZn . The O1s core-level spectra show that the peak related to oxygen vacancy defects is suppressed upon EBI. Surface morphology studies reveal that the nucleation barriers of GaZnO nanostructures are reduced upon irradiation treatment resulting in a coalescence mechanism. Third harmonic generation studies show that higher electron-beam doses lead to the occurrence of enhanced THG signals due to a drastic change in the occupation of localized defect levels. Thermally induced nonlinear optical studies depict an improved χ (3) of 1.71 × 10 −3 esu upon irradiation due to enhanced FCA induced TPA mechanism and non-radiative transitions which indicates the credibility of the grown films in photonic devices.